Digital wedding photography : - Johnson, Glen (Wiley Publishing, Inc., 2006)
Discover what makes wedding photography a unique specialty: Find out how to make people feel relaxed and comfortable while you're shooting; Explore ways to capture the emotion as well as the moment; Understand different photographic styles and adapt to your client's wishes; Prepare for all types of lighting situations; Learn appropriate etiquette for shooting in dressing rooms and during the ceremony; Know what to take when traveling abroad; Set up the perfect digital studio to process your images; Find out how to price your work realistically; See why your business skills may be more important than your photographic talent.